2018
DOI: 10.24036/jep/vol2-iss2/212
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Instrumen Penilaian Kemampuan Berpikir Tingkat Tinggi Materi Sistem Pendengaran dan Sonar SMP

Abstract: The aim of this study is to produce a higher-order thinking skills assessment instrument on the material of the hearing and sonar system for Junior high school students that are valid and reliable. Indicators of higher-order thinking skills (IKBTT) are developed based on the cognitive dimension of Bloom's Taxonomy which includes the skills to analyze (C4), evaluate (C5) and create (C6). The assessment instrument developed was a multiple choice test with open reasons. Multiple choice test with open reason is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
0
0
4
Order By: Relevance
“…Which means that this learning method factor also comes from the students themselves. This is also in line with the research (Mustikasari et al, 2018) This research shows that partially intellectual intelligence is obtained a significant value of 0.015 <0.05, emotional intelligence with a significant value of 0.013 <0.05, spiritual intelligence with a significant value of 0.025 <0.05 and learning behavior with a significant value of 0.002 <0.05. From this research, it can be concluded that the four indicators have a positive effect on accounting understanding.…”
Section: Factors Affecting the Understanding Of Semester 1 (One) Iain...supporting
confidence: 92%
“…Which means that this learning method factor also comes from the students themselves. This is also in line with the research (Mustikasari et al, 2018) This research shows that partially intellectual intelligence is obtained a significant value of 0.015 <0.05, emotional intelligence with a significant value of 0.013 <0.05, spiritual intelligence with a significant value of 0.025 <0.05 and learning behavior with a significant value of 0.002 <0.05. From this research, it can be concluded that the four indicators have a positive effect on accounting understanding.…”
Section: Factors Affecting the Understanding Of Semester 1 (One) Iain...supporting
confidence: 92%
“…Produk teruji dalam penelitian ini dikategorikan sangat valid karena mendapatkan hasil persentase tinggi (Sangat Baik) dan revisi kecil sehingga dapat digunakan untuk mengetahui kemampuan berpikir tingkat tinggi peserta didik [9]. Hal ini dikarenakan produk telah memiliki karakteristik HOTS yaitu menggunakan Kata Kerja Operasional (KKO) level C4 atau C5 atau C6, berbasis masalah kontekstual dan menggunakan stimulus (teks, gambar, tabel) sebagaimana yang diungkapkan oleh penelitian lain [10].…”
Section: Gambar 3 Desain Produk Oleh Abdul Malik [5]unclassified
“…Kemampuan berpikir kritis yang rendah pada lulusan sekolah dasar hingga perguruan tinggi masih sering dikeluhkan (Reta, 2012). Untuk mengembangkan keterampilan berpikir kritis siswa, tidak hanya melalui penggunaan model pembelajaran atau media pembelajaran saja, tetapi juga pembuatan instrumen penilaian harus merangsang siswa untuk berpikir kritis (Mustikasari et al, 2018).…”
Section: Pendahuluanunclassified